Antecedents and Consequences of Gender Swapping in Online Games. Issue 4 (18th March 2015) - Song, Haeyeop; Jung, Jaemin
Abstract This study examines the reasons underlying gender swapping and its impacts on online gaming behavior. While previous studies considered gender swapping to be an abnormal or rare exception in one's self‐presentation, this study hypothesized that people swap genders as a rational choice based on practical benefits. An online survey was conducted with 318 male players of MMORPGs in Korea. Players swapped gender in games to gain benefits from other players under the condition of anonymity rather than to represent their own gender identity. Men playing female avatars displayed more socially amiable behaviors conventionally characterized as more feminine. Moreover, players were more willing to purchase virtual goods to decorate their gender swapped avatars, mediated by their emotional attachment to their avatar.